Clinical-epidemiological profile of chemical burns in a Burn Therapy Unit (BTU) in Brazil - Murilo Sgarbi Secanho; Balduino Ferreira de Menezes; Ana Júlia de Campos Villa Da-Silveira; Ariane Aparecida Montes Fideles; Merimar Maria Chequim; Ana Beatriz Pedroso Maciel De-Oliveira; Cristiane Rocha; Aristides Augusto Palhares (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: Chemicals have a relatively low prevalence among the causes of burns. However, they are important because most accidents occur in the scope of work and in an economically active population. The objective is to perform an analysis of the profile of patients hospitalized for chemical burns in a Burn Unit. Methods: Retrospective analysis of patients hospitalized in the Burn Unit of the State Hospital of Bauru, Bauru, SP, Brazil, between 2008 and 2018. Multiple variables were analyzed, such as age, gender, chemical agent, place where the accident occurred, need for ICU stay and days of hospitalization. Results: In total, 40 (1.7%) patients were hospitalized due to chemical burn. The mean age was 35 years, with predominance of males, with 30 (75%) individuals. The main site of trauma was in the workplace, in 20 cases (50%). Based accidents were responsible for 20 (50%) admissions. The mean burned body surface was 7.5%. Eye burn occurred in 11 (27.5%) patients. Intensive care bed was required for 10 (25%) cases. When comparing accidents between acid iced substances and bases, we noted a difference in the number of ICU patients, with eight patients in lesions involving bases and two with acids (p=0.04). Conclusion: The sample and results presented in this article are similar to the world literature on the subject. We evidenced the importance of this burn in the work environment and the involvement of individuals of active age, as well as the greater severity of accidents with chemical substance.